History Now : The Presence of the Past in Contemporary Photography. - Nilsson, Bo; Petersens, Magnus af; Widbom, Mats; Zander, Ulf; Östlind, Niclas (Stockholm : Liljevalchs Konsthall, 2002)
Brodsky, Marcelo ; Bäckström, Miriam ; Bärtas, Magnus ; Doherty, Willie ; Erikson, Carl Johan ; Jaar, Alfredo ; De Keyzer, Carl ; Miesenberger, Maria ; Sedira, Zineb ; Weems, Carrie Mae ; Williamson, Sue ; Zbanic, Jasmila
ind. tent., gr. tent., coll., bibliog. p. 74-86
Zweeds & Engels
History Now : the Presence of the Past in Contemporary Photography, Liljevalchs Konsthall, Stockholm, 7 september - 13 oktober 2002 ; Passagen Linköpings Konsthall, 18 januari - 2 mars 2003 ; Dunkers Kulturhus, Helsingborg, 29 mars - 11 maj 2003 ; Midlanda Konsthall, Sundsval, 30 augusti - 26 oktober 2003 ; Konsthallen, Renneby, 8 november 2003 - 5 januari 2004
kunstcatalogus